Perspektif Mahasiswa PPG Prajabatan Terhadap Implementasi Pembelajaran Berdiferensiasi Sebagai Strategi Pemenuhan Kebutuhan Belajar Siswa - Mawardi Mawardi (JURNAL PENA EDUKASI, 2025)
Abstract: This study aims to explore the perspectives of Pre-service Teacher Professional Education Program (PPG) students on the implementation of differentiated instruction as a strategy to meet students’ learning needs. This research employed a descriptive qualitative method with data collected through in-depth interviews and documentation. The respondents consisted of four PPG pre-service students from the 2024 cohort, representing different subject areas, selected using purposive sampling. Data analysis was carried out using a qualitative thematic approach with Miles and Huberman’s interactive model, which includes data reduction to extract essential information, data display in thematic categories, and conclusion drawing with iterative verification. The findings reveal that most students hold positive perceptions of the concept and urgency of differentiated instruction in creating an inclusive learning environment. However, the respondents also highlighted several challenges in its implementation, such as limited time, insufficient resources, and a lack of technical understanding of differentiation strategies. The study concludes that more intensive training and mentoring programs are needed for pre-service teachers to effectively implement differentiated instruction in Indonesian schools.Keywords:  differentiated learning; Pre-service Teacher Professional Education Program; student learning needs Abstrak: Penelitian ini bertujuan untuk menggali perspektif mahasiswa Program Pendidikan Profesi Guru (PPG) Prajabatan terhadap implementasi pembelajaran berdiferensiasi sebagai strategi pemenuhan kebutuhan belajar siswa. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara dan dokumentasi. Responden penelitian terdiri dari empat orang mahasiswa PPG Prajabatan angkatan 2024 dari bidang studi berbeda, yang dipilih melalui teknik purposive sampling. Analisis data dilakukan dengan menggunakan pendekatan analisis tematik kualitatif model interaktif Miles dan Huberman, yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa mayoritas mahasiswa memiliki pemahaman yang positif terhadap konsep dan pentingnya pembelajaran berdiferensiasi dalam menciptakan lingkungan belajar yang inklusif. Namun para responden juga mengungkapkan berbagai tantangan dalam implementasinya, seperti keterbatasan waktu, sumber daya, serta kurangnya pemahaman mendalam terkait teknik-teknik diferensiasi. Simpulan dari penelitian ini menekankan perlunya pelatihan dan pendampingan yang lebih intensif bagi calon guru agar mereka mampu menerapkan pembelajaran berdiferensiasi secara efektif di lingkungan pendidikan Indonesia.Kata kunci: kebutuhan belajar siswa; pembelajaran berdiferensiasi; PPG Prajabatan